Pengaruh ROA, ROE dan EPS Terhadap Return Saham Perusahaan Sido Muncul Tbk. Tahun 2015-2023 - Neila Musfiatul Li'ala; Tiara Widya Antikasari (Niqosiya: Journal of Economics and Business Research, 2024)
According to financial theory, ratios such as ROA, ROE, and EPS should reflect good financial performance if they are high. However, in practice, the high ratio value of Sido Muncul Tbk. does not always correlate with the return on shares produced. This discrepancy creates confusion among investors and analysts as to how accurately these ratios reflect the actual condition of the company. This study examines the effect of ROA, ROE, and EPS on stock returns in Sido Muncul Tbk., which is listed in JII. This study uses a quantitative research method using secondary data. Data were collected through documentation and literature studies using the quarterly reports of Sido Muncul Tbk. from 2015 to 2023. The independent variables are ROA, ROE, and EPS, while the dependent variables are stock returns. Samples were selected using the purposive sampling method. The data analysis was carried out with multiple regression analysis using SPSS version 25 software, with a significance level of 5% or 0.05. The results of this study show that ROA, ROE, and EPS individually have a significant effect on the return of Sido Muncul Tbk. shares in the 2015-2023 period. At the same time, these three variables also significantly affected the return of Sido Muncul Tbk. shares in the same period. The magnitude of the influence that can be explained by these three variables on stock returns is 23.1%.